2012
DOI: 10.1063/1.4758452
|View full text |Cite
|
Sign up to set email alerts
|

Varying the charge of small cations in liquid water: Structural, transport, and thermodynamical properties

Abstract: In this work, we show how increasing the charge of small cations affects the structural, thermodynamical, and dynamical properties of these ions in liquid water. We have studied the case of lanthanoid and actinoid ions, for which we have recently developed accurate polarizable force fields, and the ionic radius is in the 0.995-1.250 Å range, and explored the valency range from 0 to 4+. We found that the ion charge strongly structures the neighboring water molecules and that, in this range of charges, the hydra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…55,56 The dipole polarizabilities of 7 The parameters of the short range non electrostatic (vdW) interaction potential ǫ ii and r 0 ii for La 3+ and Lu 3+ have been obtained by a trial and error procedure starting from a reasonable ansatz reported by OPLS force field 58 and optimizing the "homonuclear" vdW parameters of the Ln 3+ ion in order to reproduce geometry of Ln 3+ (DMSO) n clusters obtained by the ab initio calculations in the gas phase. This procedure leaves unchanged the original Amoeba vdW parameters for the Oxygen atom therefore preserving the transferability of the resulting FF.…”
Section: Force Field Developmentmentioning
confidence: 99%
“…55,56 The dipole polarizabilities of 7 The parameters of the short range non electrostatic (vdW) interaction potential ǫ ii and r 0 ii for La 3+ and Lu 3+ have been obtained by a trial and error procedure starting from a reasonable ansatz reported by OPLS force field 58 and optimizing the "homonuclear" vdW parameters of the Ln 3+ ion in order to reproduce geometry of Ln 3+ (DMSO) n clusters obtained by the ab initio calculations in the gas phase. This procedure leaves unchanged the original Amoeba vdW parameters for the Oxygen atom therefore preserving the transferability of the resulting FF.…”
Section: Force Field Developmentmentioning
confidence: 99%
“…[1][2][3][4] Molecular dynamics simulations have been employed to explore the ion-water distance, coordination number, ionic diffusion, and first shell water exchange dynamics. [5][6][7][8][9][10][11] Exchange dynamics is crucial to characterize the hydration structure and transport properties 12 of highly charged ions and it is thus important to take into account the coexistence of different coordination numbers. 13,14 Density Functional Theory (DFT)-based molecular dynamics simulations of ion hydration in liquid water can at the same time describe the interactions from first principles and explicitly consider bulk properties.…”
Section: Introductionmentioning
confidence: 99%
“…Above the transition, the dielectric friction mechanism originating from dipolar ordering should play a critical role in ion dynamics. Therefore, we consider that the regimes below and above the transition should correspond to the Stokes and dielectric friction regimes, respectively [34].…”
Section: Structural Transition Of Hydration Shell: Translational Orde...mentioning
confidence: 99%